2010
DOI: 10.1002/pip.945
|View full text |Cite
|
Sign up to set email alerts
|

The use of Ti meshes with self‐organized TiO2 nanotubes as photoanodes of all‐Ti dye‐sensitized solar cells

Abstract: This paper reports a simple and facile method for directly growing self-organized TiO 2 nanotubular arrays around the whole Ti mesh by electrochemical anodization in organic electrolytes and their application in all-Ti dye-sensitized solar cells (DSSCs). Compared with the traditional fluorine-doped tin oxide (FTO)-based DSSC and the backside illuminated DSSC, this type of DSSC showed advantages such as low resistance, cheap fabrication cost and enhanced sunlight utilization. Different thicknesses of nanotubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…We focused on structures and fabrication process of transparent conductive oxide less DSCs (TCO-less DSCs), where porous metal electrodes are fabricated at the back side of titania/dye layers as back-contact structures as shown in Fig.1. [3][4][5][6][7] We have already reported flat type, fiber type, and cylinder type dye sensitized solar cells [8][9][10][11][12]. In this report, how to optimize the structure for each cell is discussed.…”
Section: Introductionmentioning
confidence: 96%
“…We focused on structures and fabrication process of transparent conductive oxide less DSCs (TCO-less DSCs), where porous metal electrodes are fabricated at the back side of titania/dye layers as back-contact structures as shown in Fig.1. [3][4][5][6][7] We have already reported flat type, fiber type, and cylinder type dye sensitized solar cells [8][9][10][11][12]. In this report, how to optimize the structure for each cell is discussed.…”
Section: Introductionmentioning
confidence: 96%
“…3 In addition, it is not easy to fabricate the TCO layer inside of a curved glass, which limits the shape of the solar cells. [8][9][10][11][12] Fan et al have also reported the DSC based on Ti mesh electrode with 1.49% efficiency. [4][5][6][7] Figure 1 shows a representative TCO-less DSC structure.…”
Section: Introductionmentioning
confidence: 99%
“…having nearly the similar photoconversion efficiency as compared with that of TCO‐based DSSCs . Novel types of TCO‐less DSSCs, where porous TiO 2 layers are fabricated on metal mesh electrodes have been reported in the recent past . Fan et al .…”
Section: Introductionmentioning
confidence: 99%